2016
DOI: 10.1111/tmi.12804
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcomes of over 1000 patients on second‐line, protease inhibitor‐based antiretroviral therapy from four public‐sector HIV treatment facilities across Johannesburg, South Africa

Abstract: ObjectivesTo report predictors of outcomes of second‐line ART for HIV treatment in a resource‐limited setting.MethodsAll adult ART‐naïve patients who initiated standard first‐line treatment between April 2004 and February 2012 at four public‐sector health facilities in Johannesburg, South Africa, experienced virologic failure and initiated standard second‐line therapy were included. We assessed predictors of attrition (death and loss to follow‐up [≥3 months late for a scheduled visit]) using Cox proportional h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 23 publications
7
21
0
Order By: Relevance
“…The study participants of 26 studies were adults [19, 2325, 27, 34, 40, 4260], while that of 2 studies [22, 61] and 5 studies [6, 41, 6264] were children and mixed age groups, respectively. Sixteen studies (n = 16) were from southern Africa [23, 27, 43, 4552, 57, 58, 60, 62, 64]; 7 studies were from eastern Africa [22, 34, 40, 53, 55, 61, 63]; 5 studies were from western Africa [25, 41, 42, 44, 54]; and 5 studies were from mixed regions in SSA [6, 19, 24, 55, 59]. The second-line HIV treatment regimens received by the study participants were PI-based, 18 of them with ritonavir-boosted PI-based ART [24, 25, 27, 40, 42, 44, 45, 48, 49, 5256, 58, 60, 61, 63] and 15 of them with no ritonavir in their PI-based ART regimens [6, 19, 22, 23, 34, 41, 43...…”
Section: Resultsmentioning
confidence: 99%
“…The study participants of 26 studies were adults [19, 2325, 27, 34, 40, 4260], while that of 2 studies [22, 61] and 5 studies [6, 41, 6264] were children and mixed age groups, respectively. Sixteen studies (n = 16) were from southern Africa [23, 27, 43, 4552, 57, 58, 60, 62, 64]; 7 studies were from eastern Africa [22, 34, 40, 53, 55, 61, 63]; 5 studies were from western Africa [25, 41, 42, 44, 54]; and 5 studies were from mixed regions in SSA [6, 19, 24, 55, 59]. The second-line HIV treatment regimens received by the study participants were PI-based, 18 of them with ritonavir-boosted PI-based ART [24, 25, 27, 40, 42, 44, 45, 48, 49, 5256, 58, 60, 61, 63] and 15 of them with no ritonavir in their PI-based ART regimens [6, 19, 22, 23, 34, 41, 43...…”
Section: Resultsmentioning
confidence: 99%
“…Among the 181,921 individuals on ART in Rwanda [9], 174,252 (95.8%) received first-line ART and 7625 (4.2%) received second-line ART by 31st December 2016 while 44 patients were on third line ART [16]. Figure 1 presents a flow diagram of the second line ART Rwanda study sites and the patient selection process.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…The need for second-line treatment has been growing as treatment scale up has continued, but there is little robust data on outcomes among patients who have already failed a first-line regimen. 34 With data on 1435 patients on second-line ART between 2004 and 2013, we found that a low CD4 count (<50 cells/mm 3 ) at the time of switch was strongly predictive of mortality (adjusted HR (aHR) vs ≥200 cells/mm 3 : 3.76; 95% CI: 1.87 to 7.57) as was a high viral load (≥50 000 copies/mL vs 1000–4999 copies/mL aHR: 2.01; 95% CI: 1.07 to 3.77). 33 The results suggest that earlier switch would likely benefit patients failing first-line before disease progresses to severe immunosuppression.…”
Section: Findings To Datementioning
confidence: 99%